Penerapan Bimbingan Kelompok untuk Mengurangi Perilaku Bullying di Sekolah - Ega Julianti Palangiran; Reilianti Randan; Yehuda Linting (Nubuat : Jurnal Pendidikan Agama Kristen dan Katolik, 2026)
Bullying in schools continues to be a serious concern that adversely impacts students’ psychological well-being, social relationships, and academic performance. Factors such as low empathy, inadequate social skills, and limited environmental control contribute significantly to this behavior. This study seeks to examine the implementation of group guidance as an approach to reducing bullying among students. A qualitative descriptive method was utilized, involving participants consisting of students identified as bullying perpetrators, school counselors, and victims. Data collection techniques included interviews, observations, and documentation, which were analyzed through processes of data reduction, data presentation, and conclusion drawing. The results reveal that group guidance leads to positive behavioral changes in students, such as enhanced empathy, greater self-awareness, and improved communication and social interaction abilities. Furthermore, a reduction in both verbal and social bullying behaviors was observed. The group dynamics established during the sessions enabled students to better understand the consequences of their actions and gain insights from the experiences of others. These findings imply that group guidance can serve as an effective and sustainable strategy for preventing and managing bullying in school settings.